Gestión de riesgos del trabajo aplicada a las actividades de turismo de aventura en la reserva de producción faunística de Chimborazo - Montesdeoca, Mayra (2018)
WORK RISK MANAGEMENT APPLIED TO ADVENTURE TOURISM ACTIVITIES IN THE CHIMBORAZO FAUNA PRODUCTION RESERVE, MITIGATES THE RISKS TO THE THAT THE GUIDES ARE EXPOSED ABSTRACT: The research is risk-based on, physical, ergonomic and psychosocial in the tourism guides that perform climbing and cycling, the main is to demonstrate how the Work Risk Management applied to adventure tourism activities in the Chimborazo Fauna Production Reserve, mitigates the risks to the that the guides are exposed, through the management program. The theoretical foundation is based on the indicators of the operationalization of the hypothesis that contains the following topics: Risk management, risk assessment, Matrix GTC45, physical risk, Fanger method, extreme temperatures, thermal sensation, ArcGis, personal protection equipment, risk ergonomic, forced postures, REBA method, effects, psychosocial risk, questionnaires istas 21, effects and preventive measures, training programs. The methodology is based on the pre-experimental design, the type of research is applied and the deductive method was used which includes the application, understanding, and demonstration. The chosen population are the guides of adventure tourism of the Chaski club of the Federation of Andinism being a total number of 13 workers. Alternative alignments with the application of the FANGER, Comfort Thermal, ArcGis, REBA, ISTAS 21, Cold Feeling methods, indicated the level of risk and with this assessment, the Work Risk Management Program applied to tourism activities was established. of adventure in the Wildlife Production Reserve of Chimborazo to mitigate the risks to which the guides are exposed. This program consists of the use of a thermal sweater to minimize extreme temperatures, training of forced postures, participation and integration for psychological demands. To test the hypothesis, the Chi Square test was used with the data obtained before, for example in the Fanger method, the values obtained are -7.08, -11.99, -27.02 of the PMV, indicating that the environmental situation is inadequate but with the use of a thermoregulation suit the levels goes up to 0.21; 0.36; 0.48, etc. corresponding to satisfactory levels. In the second case in the application of the Reba method in forced positions the ranges of the risk level is from 8 to 10 indicating a high risk and after the corrective measures the values decreased from a range of 4 to 7 indicating that the level is acceptable. And finally the psychosocial risk with high levels in psychological demands and job insecurity obtaining values of 85% being this unfavorable for health, the results after the corrective measures the risks decreased to 31% and 69%, in this way we can conclude that the management program mitigates the risks to which the tour guides are exposed when carrying out mountaineering and cycling activities in the protected area, recommending that they continue monitoring and increasing health surveillance programs in order to work from a safe way always looking for the safety of the worker.